Samuel W. Dike papers - Dike, Samuel W. (Samuel Warren), 1839-1913.; United States. Bureau of Labor
Correspondence, speeches, writings, annual reports, articles, lecture notes, family papers, newspaper clippings, printed matter, and other papers relating primarily to Dike's activities as a Congregational minister and social reformer. Chiefly correspondence with members of the National Divorce Reform League (after 1897 the National League for the Protection of the Family) and other social reformers pertaining to Dike's responsibilities as corresponding secretary for both leagues. Subjects include attitudes toward society and societal problems, especially attitudes toward the family in society. Topics include divorce, marriage, Mormons and polygamy, temperance, the home study movement in the Congregational Church, and the elections of 1884, 1888, and 1892. Includes articles written by and about Dike; his unpublished autobiography; A Report on Marriage and Divorce in the United States, 1867-1886, published in 1889 by the U.S. Bureau of Labor; and material on temperance published by the Committee of Fifty for the Investigation of the Liquor Problem and the Woman's Christian Temperance Union. Correspondents include Herbert Baxter Adams, Newton Diehl Baker, Francis Greenwood Peabody, and Carroll Davidson Wright.
Smithsonian Institution.
Congregational minister and social reformer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Select index of correspondents available in the Library of Congress Manuscript Reading Room and at
Keywords: Adams, Herbert Baxter, -- 1850-1901 -- Correspondence; Baker, Newton Diehl, -- 1871-1937 -- Correspondence; Peabody, Francis Greenwood, -- 1847-1936 -- Correspondence; Wright, Carroll Davidson, -- 1840-1909 -- Correspondence; Dike family; Committee of Fifty for the Investigation of the Liquor Problem; National Divorce Reform League (U.S.); National League for the Protection of the Family (U.S.); Woman's Christian Temperance Union; Alcoholism -- United States; Congregational churches -- United States; Congregational churches -- Education -- United States; Divorce -- United States; Domestic relations -- United States; Families -- United States; Elections -- United States -- 1884.; Elections -- United States -- 1888.; Elections -- United States -- 1892.; Marriage -- United States; Mormon Church; Mormons; Polygamy; Social problems -- United States; Temperance -- United States; United States -- Social conditions -- 1865-1918.; Clergy; Reformers